Comparative Immunomodulatory Activity of Nigella sativa L. Preparations on Proinflammatory Mediators: A Focus on Asthma - Koshak, Abdulrahman E.; Yousif, Nizar M.; Fiebich, Bernd L.; Koshak, Emad A.; Heinrich, Michael (Frontiers in Pharmacology, 2018)
Introduction: A range of traditional and commercial preparations of NS is frequently used in the treatment of several inflammatory diseases. Often, these preparations have poor preclinical characterization that may lead to variable pharmacological effects. Objective: To assess the in vitro effects of different chemically defined preparations of NS on some asthma-related mediators of inflammation. Methods: Different NS preparations were obtained by either seed extraction with a spectrum of solvents ranging from lipophilic to hydrophilic, or commercial products were collected. The TQ concentration of NS was analyzed by HPLC. Immunomodulatory activity was assessed by the release of mediators (IL-2, IL-6, PGE2) in primary human T-lymphocytes, monocytes, and A549 human lung epithelial cells. Results: Ten distinct NS preparations showed variability in TQ concentration, being highest in the oily preparations extract-7 (2.4% w/w), followed by extract-10 (0.7%w/w). Similarly, the release of mediators was varied, being greatest in extract-7 and 10 via significantly (<0.05) suppressing IL-2, IL-6, and PGE2 in T-lymphocytes as well as IL-6 and PGE2 in monocytes. Also, PGE2 release in A549 cells was significantly enhanced by both extracts. Conclusion: The TQ concentration and in vitro activity were variable among the different NS preparations. TQ-rich oily NS preparations produced potent favorable immunomodulation in asthma inflammation and can be used in future studies.